Peanut plant response to lepidopterous pests defoliation and determination of the economic injury level - Pinto, José Ricardo Lima [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
World agriculture has been undergoing several changes, driven mainly by the integration of new technologies, with the objective of guaranteeing food security and sustainable production systems. However, for some crops, such as peanuts, there is a lack of knowledge to provide the correct adoption of innovative pest management practices. Therefore, due to the lack of studies regarding peanut plants response to defoliation caused by lepidopterous pests and the absence of tools that help producers to determine the ideal moment for control decision-making of these insects, the present work aimed to establish the basis for control decision-making to the main lepidopterous pests that occur in Brazilian peanut crops. Thus, in Chapter II we characterized, over two peanut crop seasons, the abundance of species associated with peanuts and their population fluctuations. We observed that Stegasta bosqueella (Chambers, 1875) (Lepidoptera: Gelechiidae) and the genus Spodoptera are more abundant, with greater occurrence during the bloom/pegging stage (41 ± 70 Days After Planting (DAP)) and pod/setting stage (71 ± 100 DAP). Once we identified the most abundant species, in Chapter III, we evaluated the biological aspects and feeding behavior of the species, S. bosqueella and Spodoptera cosmioides (Walker, 1858) (Lepidoptera, Noctuidae) under two of the main peanut genotypes currently adopted in Brazil, the IAC 503 and the IAC OL3. We concluded that the foliage consumption of S. cosmioides was 31.5 and 27.8 times greater than that observed for S. bosqueella, in the IAC 503 and IAC OL3 genotypes, respectively. Furthermore, the development of S. bosqueella was superior under IAC 503, while, for S. cosmioides, IAC OL3 provided better resources for larval development. After quantifying the foliar consumption potential of the most abundant species in Brazilian peanuts, we characterized in Chapter IV, through gas exchange parameters and hyperspectral remote sensing, how peanut plants respond to herbivory by S. bosqueella and S. cosmioides. Finally, in chapter V we determined the economic injury level (EIL) for S. bosqueella and S. cosmioides in peanuts at different stages of crop development. Thus, we verified that the economic injury level for S. bosqueella is 14.65, 77.96 and 36.30 larvae per plant in the early vegetative, bloom/pegging and pod/setting stages, respectively. For S. cosmioides the economic injury level is 0.74, 2.48 and 1.16 larvae per plant in the early vegetative, bloom/pegging and pod/setting stages, respectively. The generated results will allow extension personnel, producers, and consultants to make more assertive management decisions when dealing with peanut defoliation.

A agricultura mundial tem sofrido diversas transformações, baseadas principalmente na integração de novas tecnologias, com objetivo de garantir a segurança alimentar e a partir de sistemas de produção sustentáveis. Todavia, algumas culturas, como por exemplo do amendoim no Brasil, ainda carecem de estudos básicos que propiciem a correta adoção de práticas adequadas de manejo de pragas. Logo, devido à falta de estudos com relação a resposta de plantas de amendoim a desfolha provocada por lepidópteros pragas e ausência de ferramentas que auxiliem os produtores a determinar o momento ideal para tomada de decisão no controle desses insetos, o presente trabalho teve como objetivo estabelecer bases para a tomada de decisão de controle dos principais lepidópteros pragas que ocorrem na cultura do amendoim no Brasil. Dessa forma, no capítulo II caracterizamos, ao longo de duas safras de cultivo do amendoim, a abundância das espécies associadas ao amendoim e sua flutuação populacional. Observamos que Stegasta bosqueella (Chambers, 1875) (Lepidoptera: Gelechiidae) e o gênero Spodoptera são mais abundantes, com maior ocorrência durante a fase de floração (41 ± 70 Dias Após o Plantio (DAP)) e formação da vagem (71 ± 100 DAP). Uma vez que identificamos as espécies mais abundantes, no Capítulo III, avaliamos os aspectos biológicos e o comportamento alimentar das espécies, S. bosqueella e Spodoptera cosmioides (Walker, 1858) (Lepidoptera, Noctuidae) sob dois dos principais genótipos de amendoim atualmente adotados no Brasil, o IAC 503 e o IAC OL3. Concluímos que o potencial de consumo de folhagem para S. cosmioides foi 31,5 e 27,8 vezes maior, do que o observado em S. bosqueella, nos genótipos IAC 503 e IAC OL3, respectivamente. Além disso, o desenvolvimento de S. bosqueella foi superior sob IAC 503, enquanto, para S. cosmioides, IAC OL3 proporcionou melhores recursos 2 para o desenvolvimento larval. Após quantificar o potencial de consumo foliar das espécies mais abundantes em amendoim no Brasil, caracterizamos no capítulo IV, por meio de parâmetros de troca gasosa e sensoriamento remoto hiperespectral, como as plantas de amendoim respondem a herbivoria por S. bosqueella e S. cosmioides. Por fim, no capítulo V nós determinamos o nível de dano econômico (NDE) para S. bosqueella e S. cosmioides em amendoim, em diferentes estágios de desenvolvimento da cultura. Dessa forma, verificamos que o nível de dano econômico para S. bosqueella é de 14,65, 77,96 e 36,30 larvas por planta nos estágios vegetativo inicial, floração/frutificação e Formação e fixação de vagens, respectivamente. Já para S. cosmioides, o nível de dano econômico é de 0,74, 2,48 e 1,16 larvas por planta nos estágios vegetativo inicial, floração/frutificação e Formação e fixação de vagens, respectivamente. Os resultados gerados permitirão que extensionistas, produtores e consultores tomem decisões de manejo mais assertivas ao lidar com a desfolha do amendoim.
Resposta de plantas de amendoim à desfolha por lepidópteros pragas e determinação do nível de dano econômico
Keywords: Pest control; Amendoim; Spodoptera; Floração; Flowering; Controle de pragas